(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2023)
This study sought to clarify the transformation and succession of the historical environment of Cakranegara, a historical Indonesian city based on the following viewpoints: 1) transformation of building lots and their uses; 2) utilization of space on the streets; and 3) proposing appropriate indices to evaluate the historical environment of Cakranegara. The major findings were: 1) the transformation of the spatial structure of the city can be evaluated by analyzing the relationship between the change of building lots and their uses. The tendency of splitting or consolidating lots varies depending on land use type and location; however, almost half of the building lots have retained their original size; 2) the utilization of public space in Cakranegara can be analyzed and evaluated using seven categories of objects, three time scales, three types of ownership, and five categories of open space; 3) usage of Tagtagan, which is a space installed along both sides of a street, has transformed from a space for religious activities and planting trees to a space with multiple uses for daily living activities; and 4) public space is characterized by a dualistic spatial structure – space for commercial/transportation uses and space for residential uses – based on road hierarchies.